2023
DOI: 10.1007/s42448-023-00157-w
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Violence Research Across Multiple Family Generations and with Young Children: Findings from a Mixed-Methods Pilot Study in South Africa

Abstract: This paper presents findings from a pilot study focused on examining intergenerational violence in a three-generation sample, which included young children, in a rural area of South Africa. The aims of the pilot study were to investigate the feasibility of participant recruitment, consent, and interviewing; length and burden of the study questionnaires; appropriateness and acceptability of the measures used; and young children’s (age 4–7) ability to comprehend the measures and participate meaningfully in inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…We found that children as young as 4 years old could participate in our pilot study [ 34 ]. With very young children, researchers have highlighted that verifying the information they provide may be difficult, and that data elicited may not be a genuine reflection of the way they understand the world [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that children as young as 4 years old could participate in our pilot study [ 34 ]. With very young children, researchers have highlighted that verifying the information they provide may be difficult, and that data elicited may not be a genuine reflection of the way they understand the world [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study was undertaken in rural Mpumalanga in South Africa (July–October 2021) [ 34 ]. The study comprised a convenience cross sectional sample drawn from residents in the area of young adults aged 22–30 years, children aged 4–7 years, and former caregivers of the young adults.…”
Section: Methodsmentioning
confidence: 99%
“…In preparation for a longitudinal multigenerational cohort study on mechanisms that underlie the intergenerational transmission of violence ( Meinck et al, 2023 ), a pilot study was conducted in rural Mpumalanga in South Africa from July to October 2021. The study consisted of a convenience sample drawn from residents in the area where the main study was to be undertaken; the pilot study recruited young adults aged 22 to 30 years, children of young adults aged 4 to 7 years, and caregivers of the young adults ( Franchino-Olsen et al, 2023 ). Ethical approval was granted by the University of Edinburgh School of Social and Political Science Research Ethics Committee (264227), the University of the Witwatersrand Human Research Ethics Committee (M190949), and the North-West University Health Research Ethics Committee (NWU-00329-20-A1).…”
Section: Methodsmentioning
confidence: 99%
“…In preparation for a longitudinal multigenerational cohort study on mechanisms that underlie the intergenerational transmission of violence (Meinck et al, 2023), a pilot study was conducted in rural Mpumalanga in South Africa from July to October 2021. The study consisted of a convenience sample drawn from residents in the area where the main study was to be undertaken; the pilot study recruited young adults aged 22 to 30 years, children of young adults aged 4 to 7 years, and caregivers of the young adults (Franchino-Olsen et al, 2023)…”
Section: Background On Pilot Studymentioning
confidence: 99%
See 1 more Smart Citation